Consular aspects of surrogate gestation under International Private Law - Pertusa Rodríguez, Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Article 10(1) of law 14/2006 establishes the nullity of contracts of surrogate gestation in Spain. DGRN Rule of October the 5th of 2010 devises a mechanism to receive in a consular civil registry foreign resolutions that establishes filiations through surrogate gestation. The Rule requires that the filiation will be determined by a court ruling. The person in charge of the consular civil registry has a wide discretion when registering this ruling as well as considering if an exequatur is needed or a direct recognition is adequate.